Graph Symmetry 1997
DOI: 10.1007/978-94-015-8937-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Graph homomorphisms: structure and symmetry

Abstract: This paper is the first part of an introduction to the subject of graph homomorphism in the mixed form of a course and a survey. We give the basic definitions, examples and uses of graph homomorphisms and mention some results that consider the structure and some parameters of the graphs involved. We discuss vertex transitive graphs and Cayley graphs and their rather fundamental role in some aspects of graph homomorphisms. Graph colourings are then explored as homomorphisms, followed by a discussion of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 97 publications
0
142
0
Order By: Relevance
“…A review of graph homomorphisms, especially with applications to colorings, is in Hahn and Tardif [11]. These studies do not include studies of homomorphisms with property (3).…”
Section: Introductionmentioning
confidence: 99%
“…A review of graph homomorphisms, especially with applications to colorings, is in Hahn and Tardif [11]. These studies do not include studies of homomorphisms with property (3).…”
Section: Introductionmentioning
confidence: 99%
“…, p}, i.e., V (K p,q ) = The fractional chromatic number of K p,q is clearly at most p/q, and it is not hard to show that it is actually equal to p/q. The definition of the fractional chromatic number yields the following proposition which can also be found, e.g., in [11]. We include a short proof for the sake of completeness.…”
Section: Universal Graphsmentioning
confidence: 75%
“…Welzl [21] showed that the core of a vertex-transitive graph is vertex-transitive; see [11,Theorem 3.7]. More general statements are true; for example, the properties of edge-transitivity and non-edge-transitivity are inherited by cores as well.…”
Section: Cores and Hullsmentioning
confidence: 99%